Sustainable maintenance of navigation channel / [electronic resource] - 187259 Oladokun Sulaiman Olanrewaju (2006)
Thesis (Sarjana Kejuruteraan (Mekanikal Teknologi Marin)) - Universiti Teknologi Malaysia, 2006